Managing Hyperactive Children In An Islamic Kindergarten: Teachers' Strategies and Islamic Values-Based Practices - Nusir, Lidia; Husna, Husna; Putri, Risa Nailis; Andini, Riddo; Syahminal, Syahminal (PIAUD Universitas Islam Negeri Sunan Kudus, 2026)
Hyperactive children often exhibit excessive physical activity, difficulties in maintaining attention, and behaviors that may disrupt classroom learning. These characteristics require teachers to implement appropriate strategies that support children's learning and development. This study aims to explore teachers’ strategies and Islamic values-based practices for managing hyperactive children at Al-Kahira Islamic Kindergarten, Sintuak Toboh Gadang. Using a qualitative case study design, data were collected through classroom observations, teacher interviews, and document analysis. The findings reveal five key strategies employed by teachers: (1) individualized approaches and empathetic communication, (2) consistent enforcement of classroom rules, (3) active play-based learning activities, (4) positive reinforcement through Islamic rewards and moral encouragement, and (5) collaboration among teachers, parents, and the school. The study further shows that Islamic values, including raḥmah (compassion), ṣabr (patience), amanah (responsibility), and at-ta‘āwun (collaboration), underpin teachers’ practices in supporting hyperactive children. These strategies were found to contribute to improved behavioral regulation, concentration, and social-emotional development among the children. The findings highlight the potential of integrating Islamic values into inclusive early childhood education practices and provide insights for educators working with hyperactive children in Islamic educational settings.